Experimental Study of the Effects of Inclusion of Rectangular-Cut Twisted Tapes on Heat Transfer and Pressure Drop in a Round Tube - Ruengpayungsak, K.; Kumar, Manoj; Chuwattanakul, V.; Eiamsa-ard, S. (My University, 2019)
Twisted tape inserts were used as swirl generators in the flow through a tube for enhancing heat transfer. Twisted tapes have commonly been applied in many thermal applications used in industry. Several modified twisted tapes have been investigated for improving the thermal performance of heat exchangers. The effects in tubes with modified rectangular-cut twisted tape (RC-TT) inserts with various free-spacing ratios (s/w = 2.0, 2.5, 3.0, 3.5 and 4.0) and edge–width ratios (t/W = 0.1, 0.15, 0.2 and 0.25) on heat transfer and pressure losses are reported. The RC-TT used in this work had a fixed thickness of 1.2 mm, width of 60 mm, length of 2000 mm and twist ratio (y/W) of 3.0. Experiments were performed over a range of Reynolds numbers, 10,000 ≤ Re ≤ 20,000, using air as a test fluid. A tube with a classical/typical twisted tape was also tested for comparison. In all cases, the Nusselt number tended to increase with the Reynolds number, while the friction factor and thermal performance showed the opposite trend. For the rectangular-cut twisted tape inserts, the friction factor and Nusselt number decreased, while thermal performance increased with increasing free-spacing ratios (s/w) and edge–width ratios (t/W). Furthermore, the maximum thermal performance was achieved at the lowest free-spacing ratio (s/w), edge–width ratio (t/W) and Reynolds number (Re).
Keywords: Heat exchanger; Heat transfer; Heat transfer enhancement; Rectangular-cut twisted tape; Swirl flow; Twisted tape insert